DAMPAK TEKNOLOGI ARTIFICIAL INTELLIGENCE PADA PROFESI AKUNTANSI - Putri Dwima Ernis,; Padli Pirdaus, (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2022)
The development of Artificial Intelligence technology has changed the accounting profession. This research provides a comprehensive overview of the latest developments in Artificial Intelligence, Big Data, Machine Learning used in business practices in the accounting profession around the world. The author explores the evolution of the accounting profession following the latest technological developments and then assesses the impact of its future developments and large companies that use new technology. Furthermore, the research used is a descriptive qualitative approach. The researcher used descriptive qualitative research and the data taken in the form of secondary data from previous research. This study provides an overview of how accounting professionals respond to these technological developments and provides further discussion on what the accounting profession should do to face the challenges of change caused by technological developments.